ETR 300 : FunBeez Toy Store / Noor Syarizan Mohd. Said ... [et al.] - Mohd. Said, Noor Syarizan; Jamil, Erlina; Abdul Muttalib, Nur Annisa; Shabudin, Hamizah; Azami, Mariam Jamillah (2002)
FunBeez Enterprise, which commences on I st January 2003, is a business which focuses on fulfilling and catering the needs of our customers by providing them products and services. Our business falls under the category of medium-level business, as we play the role of sub-contractors who ordered our products from giant companies and manufacturers and sell them to our customers. In short, we acted as intennediaries, between the buyers and the manufacturers. Based on numerous studies and a11alysis done by the researchers worldwide, education from an early age is extremely vital to guarantee a child to be an all-rounder, being able to handle any situation given. That is why we at FunBeez try to assist the parents in educating their children by offering them a large selection of toys, because we think that toys are the tools of education and learning in a child's early years. At FunBeez, we believe in offering great selection and value. That's why we have developed an exclusive line of high quality, affordable toys that can only be found at FunBeez. For the best learning toys around, F1111Beez offers fun, interactive and educational toys that everyone will love, in line with the Government's desire to see the upsurge in the number of Bumiputra entrepreneurs. We believe i.n letting imaginations soar. So that's why we choose to reach out to the people surrounding us by making their dreams come true and transform their imaginations to life. FunBeez foatures toys that are educationally beneficial as well as a whole lot of fun. We also provide a place for the parents to read infonnative articles and product reviews written in by teachers. Fun.Beez is simply put as the "family store", assisting the children through their growing years and helping the adult reminisce the kid in them